Clinical and Classical Risk Factors Profiles of Coronary Artery Disease Patients Aged 40 Years or Less (Journal of Enam Medical College, 2024)
Background: Cardiovascular diseases (CVD) have increased greatly in the last 2 decades in low- and middle-income countries. Among the CVDs, atherosclerotic coronary artery disease is rare in young adults aged 40 years or less. However, South Asia is among the top 3 of the countries with highest proportion of cases of first acute coronary syndrome events occurring at age 40 years or less. Five classical risk factors account for 80% of population attributable risk in overall population and the impact of these risk factors are remarkable in young adults. Objective: To explore the prevalence of the classical risk factors of coronary artery disease among patients of ischemic heart disease aged 40 years or less. Materials and Methods: This crosssectional retrospective analysis included 140 patients who had coronary angiography for definite and probable ischemic heart disease at the department of Cardiology of Enam Medical College between July 2012 and December 2020. Clinical and classical risk factor profiles were recorded by recording height, weight and self-reported hypertension, diabetes mellitus, hyperlipidemia, tobacco smoking, family history of premature coronary artery disease, supplemented by testing for diabetes and hyperlipidemia as necessary. Coronary angiography was performed and analyzed in the same center as per standard protocol. Results: Of the 140 patients included in the study, 85% were males. The age range was 18−40 years, with a mean age 35.90 (SD 4.05) years, and 59.28% were in the 36−40 years age group. Indications for coronary angiography were: acute myocardial infarction in 69.28%, unstable angina in 3.57%, stable angina in 20% and other miscellaneous causes in 7.155 (e.g., heart failure, arrhythmia, prior PCI and positive exercise stress test). A prior history of myocardial infarction was present in 25.43%. Coronary angiogram revealed single vessel disease in 39.29%, double vessel disease in 25.72% and triple vessel disease in 23.57%. Normal Coronaries were found in 9.28% and myocardial infarction with non-obstructed coronary arteries (MINOCA) in 2.14%. Of the risk factors, hypertension was present in 38.57%, smoking in 34.91%, diabetes mellitus in 27.14%, a family history of coronary artery disease in 19.29% and dyslipidemia in only 15.71%. Obesity was present in 12.86%, while 37.86% were overweight. Altogether 57.72% had excess body weight, making it the most prevalent factor contributing to ischemic heart disease. Clustering of 2 or more risk factors was seen in 45% of patients, while 45.71% had only one risk factor and 9.29% having none. A history of substance abuse was found in only 03 (2.14%) patients, 02 of them having additional traditional risk factors. Conclusion: In patients aged up to 40 years with ischemic heart disease, significant coronary artery disease burden was seen, including a significant proportion with multi-vessel disease. Traditional risk factors of coronary artery disease were found to play a significant role among them. Weight related problems (overweight and obesity) was seen to be significant. Further epidemiological studies with pooled data from all the tertiary care centers need to be carried out.J Enam Med Col 2021; 11(3): 147−155